The Influence of Vitamin K Levels on Blood Coagulation Factors After Tooth Extraction in Hemophilia Patients - Indeswati Diyatri; Muhammad Hibban Qadhafi; Haura Destina Anandhiyah; Muhamad Nabil Rabbani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hemophilia is a genetic disorder resulting from impaired blood clotting. This disorder can be caused by coagulation factor abnormalities due to a deficiency of clotting factors, including vitamin K. A lack of vitamin K disrupts the coagulation process, increasing the tendency for bleeding. This article aims to determine whether there is an influence of vitamin K levels on the blood clotting factors in hemophilia patients. Searching any information needed by analyzing kinds of papers of recent research from the year of 2014 until 2024. Online databases like PubMed, ScienceDirect, Google Scholar, Scopus, and ResearchGate are utilized by inserting relevant keywords, such as hemophilia, blood clotting factors, vitamin K deficiency and extraction. From 10 articles reviewed, a relationship was identified between vitamin K levels and blood clotting factors in hemophilia patients. Individuals with severe hemophilia experience bleeding episodes characterized by delayed onset, as well as bleeding into muscles, joints, and other internal structures, including the brain. Hemophilia is typically diagnosed through the identification of low or absent levels of FVIII:C or FIX:C. The genes encoding FVIII and FIX are located on the long arm of the X chromosome. Hemophilia A and B are the only hereditary clotting disorders inherited in a sex-linked recessive pattern. Vitamin K levels can influence the blood clotting factors in hemophilia patients, particularly those factors synthesized artificially.